2020
DOI: 10.1097/md.0000000000020825
|View full text |Cite
|
Sign up to set email alerts
|

Primary bladder mucosa-associated lymphoid tissue lymphoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…However, there was no beneficial effect of surgery on patients with UB-DLBCL. There are no surgical recommendations for UB lymphomas, mainly because of the morbidity and mortality associated with surgery ( 16 ). Regarding radiotherapy, our results suggested that radiation treatment had no benefit on UT-DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no beneficial effect of surgery on patients with UB-DLBCL. There are no surgical recommendations for UB lymphomas, mainly because of the morbidity and mortality associated with surgery ( 16 ). Regarding radiotherapy, our results suggested that radiation treatment had no benefit on UT-DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment for the condition has changed over time. 2 In the past, surgical treatment, such as total cystectomy or partial cystectomy, was principally used; however, it was found that there was no difference in the recurrence rate between surgical and non-invasive treatments. Since 1990, chemotherapy or radiation therapy, which can preserve the bladder, has become the mainstay of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MALT lymphoma is a unique subtype of B-cell lymphoma predominantly involving extranodal sites, such as the stomach, orbit, conjunctiva, salivary glands, thyroid and lungs[ 2 , 5 - 7 ]. The bladder is rarely involved, accounting for only 0.2% of extranodal lymphomas[ 8 ]. The risk factors include chronic inflammation, urinary tract infections and autoimmune diseases[ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%